THE EFFECTIVENESS OF PROBLEM-BASED LEARNING WITH SOCIAL MEDIA ASSISTANCE TO IMPROVE STUDENTS’ UNDERSTANDING TOWARD STATISTICS - Yuliana Yuliana; Fery Firmansah (IKIP Siliwangi and I-MES, 2018)
The objectives of the research are (1) to develop mathematics learning through Problem Based Learning (PBL) with social media assistance in improving students’ understanding toward statistics and (2) to find out the effectiveness of PBL with social media assistance. This research is a quasi-research with cluster random sampling. The cluster random sampling was employed to determine a control class and an experimental class. After treatment for each class, post-test was done. Then, the post-test data was analyzed through a T-test. The result is the mean score of post-test in experimental class was better than that in control class. It means PBL with social media assistance is more effective than the conventional model to teach statistics. The result was supported by a questionnaire that showed learning mathematics through PBL with social media assistance got a positive response from the students.